PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN MIE KIRO KEBUMEN - Rahma Diani, Nafa Amalia (AKSIOMA : Jurnal Manajemen, 2022)
This study was conducted to determine the effect of brand image, product quality and price variables on product purchasing decisions at Mie Kiro Kebumen restaurant either partially or simultaneously and to find out which of the variables brand image, product quality and price has a greater role in influencing consumer purchasing decisions. The data used is primary data obtained through data collection techniques in the form of online questionnaires which are distributed to people in Kebumen Regency who have purchased products at Mie Kiro Kebumen, which will then be used as samples. Sampling of 100 with purposive sampling technique. The data that has been collected is then processed and analyzed using multiple linear regression, T test and F test with the help of SPSS 22 software. The results show that the brand image variable partially has no effect on consumer purchasing decisions at Mie Kiro Kebumen restaurant, but simultaneously has an effect. Product quality and price variables both partially and simultaneously affect consumer purchasing decisions at Mie Kiro Kebumen restaurant. Among the three variables, the price variable has the most role in influencing consumer purchasing decisions at Mie Kiro Kebumen restaurant